Rehabilitacija pacientov z revmatoidnim artritisom - Novak, Primož (Rehabilitacija (Ljubljana), 2011)
Rheumatoid arthritis is the most frequent inflammatory rheumatic disease in the developed world. It can affect body structures and functions and consequently causes limitations in patientćs activity and participation. The article presents a review of published studies on rehabilitation of patients with rheumatoid arthritis, based mainly on the conclusions from review articles. The review shows the effectiveness of comprehensive rehabilitation as well as of individual therapeutic methods, although the assessment of quality of evidence and the consequent grade of recommendations differs between the authors of different reviews. Therefore, additional studies are necessary in search for optimal rehabilitation program for patients with rheumatoid arthritis.
Keywords: fizikalna terapija; rehabilitacija; revmatoidni artritis; therapy; vocational rehabilitation; zdravljenje